The Relationship Between Leadership Behaviors and Volunteer Commitment: The Role of Volunteer Satisfaction - Benevene, Paula; Buonomo, Ilaria; West, Michael (Frontiers in Psychology, 2020)
Despite the relative scarcity of studies on the impact of leadership styles on satisfaction and commitment of volunteers within nonprofit organizations, this relationship plays a crucial role in fostering sustained volunteerism and volunteers’ well-being. A questionnaire was administered to more than 200 volunteers involved in delivering social service in nonprofit organizations from Central and Northern Italy. The questionnaire contained the Volunteer Satisfaction Index, the sub-scale on Affective Commitment of the Organizational Commitment Scale, nd two sub-scales of the Key Leadership Behaviors, namely: Helping people to grow and lead, and Enabling learning and innovation. Socio-demographic data were collected as well. Findings reveal that leaders’ actions oriented towards the enablement of learning and innovation have an effect on volunteers’ affective commitment, through the full mediation of volunteer satisfaction. Leaders’ actions oriented towards the growth and empowerment of volunteers, instead, did not show significant relationships with volunteer satisfaction and affective commitment.